Raman scattering in crystals with order-disorder type phase transition - Ivankiv, Ya. (Condensed Matter Physics, 1999)
The theory based on the “operator” two-time Green functions formalism applied for the construction of the polarizability operators entering the general expression for the effective cross-section of Raman scattering is developed. The presented microscopic scheme is applied to the investigation of the ferroelectrics with hydrogen bonds. На основі формалізму двочасових функцій Гріна розвинуто теорію побудови оператора поляризованості, що входить у загальний вираз для ефективного поперечного перерізу раманівського розсіяння. Представлена мікроскопічна схема використовується для дослідження сегнетоелектриків з водневими зв’язками.